Predictors and severity of intestinal ischaemia following on-pump cardiac surgery: a retrospective, propensity-matched analysis. (25th February 2022) - Wiesmueller, Felix; Bryan, Darren S; Krautz, Christian; Grützmann, Robert; Weyand, Michael; Strecker, Thomas
Abstract: OBJECTIVES: Risk factors associated with intestinal ischaemia after heart surgery have been previously explored; however, a paucity of data exists with regard to extent of intestinal ischaemia in patients requiring surgical intervention. The purpose of this study is to assess predictors of abdominal exploration and extent of ischaemia following cardiac surgery. METHODS: A retrospective single-centre study was performed at a university hospital. The patient sample included consecutive patients between 2009 and 2020 who first received cardiac and then abdominal exploration during the same hospital stay. Control group patients were identified by 1:1 propensity matching. Logistic regression was performed to identify risk factors for laparotomy. Patients of the laparotomy group were further analysed for intraoperative findings from required abdominal operations. RESULTS: A total of 6832 patients were identified, of whom 70 (1%) underwent abdominal exploration. The median time to exploratory laparotomy was 6 days with no difference between intraoperatively confirmed ischaemia versus those who underwent negative exploration. Thirty-day mortality was 51%. Prior diagnosis of COPD or administration of 2 or more vaso-inotropes during the postoperative phase was independent risk factors for exploratory laparotomy. Vaso-inotrope use was a strong independent predictor of extent of intestinal ischaemia as well as for 30-day mortality. Degree of intestinal ischaemia was also an independent predictor of 30-day mortality. CONCLUSIONS: Intestinal ischaemia is a feared complication after cardiac surgery with high mortality, often necessitating multiple abdominal procedures. Administration of 2 or more vaso-inotropes in the postoperative phase of cardiac procedure is a strong predictor for the degree of ischaemia and 30-day mortality. Abstract : Mesenteric ischaemia is a rare but potentially devestating complication following cardiac surgery.